2015
DOI: 10.1111/jar.12152
|View full text |Cite
|
Sign up to set email alerts
|

The Behaviour Problems Inventory‐Short Form: Reliability and Factorial Validity in Adults with Intellectual Disabilities

Abstract: We corroborated the factor structure underly-ing the three subscales and found the BPI-S to have adequate to good psychometric properties in a newly collected sample of adults with intellectual disabilities.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
30
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(33 citation statements)
references
References 25 publications
1
30
1
Order By: Relevance
“…Researchers also completed the Behaviour Problems Inventory – short form (BPI‐S) (Rojahn et al b; Mascitelli et al ) to measure challenging behaviour during the previous 6 months as reported by proxy informants. BPI‐S data were coded against the following definition (Bowring et al ): SIB: any item of self‐injurious behaviour is ‘challenging’ if either it is rated as severe and occurs at least weekly, or is rated as moderate but occurs at least daily.…”
Section: Methodsmentioning
confidence: 99%
“…Researchers also completed the Behaviour Problems Inventory – short form (BPI‐S) (Rojahn et al b; Mascitelli et al ) to measure challenging behaviour during the previous 6 months as reported by proxy informants. BPI‐S data were coded against the following definition (Bowring et al ): SIB: any item of self‐injurious behaviour is ‘challenging’ if either it is rated as severe and occurs at least weekly, or is rated as moderate but occurs at least daily.…”
Section: Methodsmentioning
confidence: 99%
“…Challenging behaviour was assessed at wave 3 using the Behaviour Problems Inventory for Individuals with Intellectual Disabilities – Short Form (Mascitelli et al . ). The Behaviour Problems Inventory for Individuals with Intellectual Disabilities – Short Form is the shortened version of the Behaviour Problems Inventory‐01 (Rojahn et al .…”
Section: Methodsmentioning
confidence: 97%
“…The instrument has acceptable reliability in terms of internal consistency, inter‐rater agreement and test–retest reliability (Mascitelli et al . ). For the purpose of this study, challenging behaviour is defined by the presence of a least one behaviour in any of the three domains during the previous 2 months.…”
Section: Methodsmentioning
confidence: 97%
See 2 more Smart Citations